2018
DOI: 10.1093/jas/sky152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing concentrations of an Escherichia coli phytase on the apparent ileal digestibility of amino acids and the apparent total tract digestibility of energy and nutrients in corn-soybean meal diets fed to growing pigs1

Abstract: An experiment was conducted to test the hypothesis that inclusion of increasing concentrations of an Escherichia coli phytase to a corn-soybean meal (SBM) diet results in improved digestibility of DM, GE, CP, NDF, ADF, macrominerals, microminerals, and AA. Twenty-four growing barrows (initial BW: 37.0 ± 1.4 kg) were equipped with a T-cannula in the distal ileum and placed individually in metabolism crates, and allotted to a 2-period switch-back design with 6 diets and 4 replicate pigs per diet in each period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
6
25
1
Order By: Relevance
“…The negative effect of phytase on the ATTD of GE that was observed in this experiment is in agreement with a recent meta-analysis for effects of microbial phytase on ATTD of GE (Torres-Pitarch et al, 2017). However, results of some studies also indicated that there was no effect of phytase on the ATTD of GE (Zeng et al, 2016;She et al, 2018), or that the ATTD of GE increased with supplementation of phytase to diets (Kiarie et al, 2016;Dersjant-Li et al, 2017). Thus, results of this and previous experiments indicate that the effect of microbial phytase on the AID and ATTD of GE is not consistent.…”
Section: Amino Acids and Energysupporting
confidence: 92%
See 3 more Smart Citations
“…The negative effect of phytase on the ATTD of GE that was observed in this experiment is in agreement with a recent meta-analysis for effects of microbial phytase on ATTD of GE (Torres-Pitarch et al, 2017). However, results of some studies also indicated that there was no effect of phytase on the ATTD of GE (Zeng et al, 2016;She et al, 2018), or that the ATTD of GE increased with supplementation of phytase to diets (Kiarie et al, 2016;Dersjant-Li et al, 2017). Thus, results of this and previous experiments indicate that the effect of microbial phytase on the AID and ATTD of GE is not consistent.…”
Section: Amino Acids and Energysupporting
confidence: 92%
“…The observation that there was no effect of phytase on the AID of AA is in agreement with She et al (2018), who reported that inclusion of up to 4,000 FTU of an E. coli phytase to a corn-soybean meal-based diet had no impact on the AID of AA. Likewise, addition of up to 2,000 FTU of an E. coli phytase had no effect on the AID of the majority of AA (Liao et al, 2005;Velayudhan et al, 2015).…”
Section: Amino Acids and Energysupporting
confidence: 91%
See 2 more Smart Citations
“…(Madrid et al, 2013) and amino acid digestibility through the decrease of antinutritional effects of phytate and its derivates (Cowieson et al, 2017;Zouaoui et al, 2018). Zeng et al (2014) reported an increase in the apparent ileal digestibility of DM (using 1,000 to 20,000 FTU/kg), but Zeng et al (2016) using 0 to 20,000 FTU/ kg and She et al (2018) using 0 to 4,000 FTU/ kg, did not. However, these studies used much higher levels (super-dosed levels) of phytase than those used herein (0-327 FTU/kg), and investigated ileal as opposed to total tract digestibility, the focus of this study.…”
Section: Discussionmentioning
confidence: 99%